Analisis Keterampilan Guru dalam Mengembangkan Model EEK pada Proses Pembelajaran Kelas IV SD Negeri Sampangan Tahun Ajaran 2016/2017 - Wahyuni, Nita, Drs. H. Rubino Rubiyanto, M.Pd (2017)
In the implementation of learning one of the activities to be developed is the core activity. Core activities using methods adapted to the characteristics of learners and subjects, which may include the exploration, elaboration and confirmation. A teacher must have the skills in developing learning activities using the model EEK. But in fact there are teachers who do not know how to manufacture and how lesson planbased EEK and EEK model development in the learning process in the classroom. This study aimed to describe the skills of teachers in developing a model EEK in the learning process. The method used in this research, interviews, observation and documentation. Eksplorsi activities are activities beginning will enter a new material, for example, introducing the material to be studied. In exploration activities, the students involved in the search for information using a variety of approaches and media and learning resources. In lessons always an interaction between components of learning and often experiment if the material is appropriate. Elaborsi activity is a core activity or the implementation of learning activities. In the elaboration of activities, learners are taught to read and write as well as do discussions with friends. Activity confirmation is closing activity for example, summarizes, tests, follow-up students etc. In confirmation of activities, the teacher always provide reinforcement and reflection usually orally. Teachers always checking of results of exploration learners so that teachers act as facilitators, resource persons and teachers in developing motivator. skill exploration, elaboration and confirmation activities in the lesson plan is still lacking and needs to be developed further. When viewed globally the skills of teachers in developing exploration activities, elaboration and confirmation in the fourth grade learning process is already showing good results. However, when viewed from the implementation of each indicator will be visible gap between the indicator with other indicators.